Shackling the Poor, or Effective Altruism: A Critique of the Philosophical Foundation of Effective Altruism - Ioannidis, Iraklis (Conatus - Journal of Philosophy, 2020)
Effective Altruism (EA) is both a philosophy and a movement. The main criticism on EA is that by donating to charities EA leaves fundamental moral issues such as global poverty and injustice intact. EA arguably does not promote radical institutional change which could lead to an ultimate eradication of the problems that may endanger people’s lives in the first place. In this article this critique is reinforced from a different point of view. The criticism on EA has been mainly on the performative or the empirical aspect of the movement. That is, criticism on EA focuses on evaluating the practical realisation of its mandates with little, if any, evaluation on its philosophical foundation. My aim in this paper is to extend the critique but from a different angle, that is, by going back to its philosophical underpinnings. By exploring the philosophical foundation of EA, I would like to show how EA is not authentic altruism as it is founded on the sacrifice of the Other whom is supposed to be saved.